2016
DOI: 10.1371/journal.pone.0157557
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Correlation between Heart Rate Variability and Heart Rate Demonstrated by Linear and Nonlinear Analysis

Abstract: The dynamical fluctuations in the rhythms of biological systems provide valuable information about the underlying functioning of these systems. During the past few decades analysis of cardiac function based on the heart rate variability (HRV; variation in R wave to R wave intervals) has attracted great attention, resulting in more than 17000-publications (PubMed list). However, it is still controversial about the underling mechanisms of HRV. In this study, we performed both linear (time domain and frequency do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 17 publications
10
46
0
2
Order By: Relevance
“…Heart rate in general49 and also selective heart rate reduction by ivabradine are inversely correlated to HRV, as shown in a study with conscious rats 50. Improvement of HRV with ivabradine was blocked in this model by administration of the beta-blocker propranolol or the muscarinic antagonist atropine, indicating the critical importance of the two components of the autonomic nervous system.…”
Section: Ivabradine – Mode Of Action and Pharmacologysupporting
confidence: 55%
“…Heart rate in general49 and also selective heart rate reduction by ivabradine are inversely correlated to HRV, as shown in a study with conscious rats 50. Improvement of HRV with ivabradine was blocked in this model by administration of the beta-blocker propranolol or the muscarinic antagonist atropine, indicating the critical importance of the two components of the autonomic nervous system.…”
Section: Ivabradine – Mode Of Action and Pharmacologysupporting
confidence: 55%
“…However, HRV analysis is still under investigation due to HRV characteristics that could lead to physiological misinterpretations (Osaka et al, 1993; Chiu et al, 2003). ANS modulation is linked to ANS tone (HR mean) and, as a consequence, an increase in the sympathetic activity and a decrease in the vagal tone are related to an increment in the HR and a reduction on its variability (Chiu et al, 2003; Kazmi et al, 2016). This implies that there is a physiological correlation between HRV and HR.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, major concerns have been raised regarding the influence of HR on HRV. Monfredi et al (2014) and Kazmi et al (2016) showed a nonlinear inverse relationship between HR and HRV (i.e., variability in HR decreases as HR increases), implying that HRV might simply be an indirect measure of HR (Monfredi et al, 2014). The latter authors indicated that it is possible to control for the effect of HR on HRV with a nonlinear correction.…”
Section: Physiological Responsesmentioning
confidence: 99%